Busways as a solution for transport crisis in large african cities - (:unkn) unknown (My University, 2006)
Large Sub-Saharan cities are still undergoing significant demographic growth that leads to rapid and unplanned urban sprawl. This results in an increasing transport demand and lengthening of travel distances. Urban transport services, mainly provided by small-scale operators, have many difficulties to facing distance lengthening and cannot meet the high level of demand. Some Latin American cities who were confronted with similar difficulties have developed bus transport systems based on the exclusive rights of way principle (“busways”). In Sub-Saharan cities, busways may solve the urban transport crisis because infrastructure and operating costs are lower than for other mass transit solutions such as railway systems. Busway systems are financially affordable to African cities in the form of public-private partnerships i.e. implementation of the infrastructure by the public sector and concession for operation to the private sector. In busways, the optimized use of infrastructure, vehicles and operating system make it possible to transport a great number of passengers while minimizing travel time and negative externalities generated by urban transport, so they are appropriate for major commuter corridors. Moreover, the busway alternative introduces a logic of hierarchical and complementary segments of the urban transport supply and therefore it imposes an overall vision in the organization of urban transport. Given that the busway alternative represents a qualitative improvement in urban mobility and a long-term physical imprint on the urban space, it constitutes a lever for, on the one hand, questioning the failing urban transport organization and regulation framework, and on the other hand, reorganizing the current transport supply sector. In large Sub-Saharan cities, by organizing a more effective coordination of transport supply for long-distance as well as short-distance travel, busways could thus become the core of public transport services.
Keywords: African Research